Tinjauan Hukum Islam Terhadap Undang-Undang No. 23 tahun 2002 Tentang Perlindungan Anak - Jamilia Susanti (Medina-te : Jurnal Studi Islam, 2016)
The concept of Islam toward the children protection referred to the Qur'an and as-sunna. With this reference would find clarity about aspects of children protection. As for some norms of the irregularities and crimes in assessing children protection happened in society. Children protection must go through the judicial institutions, as the material development of scientific work and material of legal considerations used as basic materials of legal decision on the children protection. In addition, the religious courts paid attention to the values of law which were alive in the society were a role of law and justice as contained in the government's decision in Law No. 23 of 2002 on the protection of children. Someone's life must be paid attention even in development of physical, mental, and spiritual. This paper concluded the concept of children protection according to Law No. 23 of 2002 on the protection of children, explained that children were creatures who must be protected from any danger that would happen, the children should grow and develop both physically and mentally. Likewise with Article 13 paragraph 1 and 2 that (1) the crimes that caused injuries and fatalities to children who did so charged to severe legal. (2) The parent or guardian nanny if committing a crime when caring for the children, so the parent or guardian nanny would get severe punishment. In Law No. 23 of 2002 in Article 1, which reads every person had the right to live grow and participate in the fair with the dignity of humanity also get protection from violence and discrimination (threatening). Meanwhile, according to Islamic law for all human life must be protected from both physical and spiritual. Because it had been required to protect both themselves and others, In Islamic law, especially in prayer command explained that the prayer for Muslims was obligatory. When the children were 10 years old it must execute the order of prayer, but if at that age did not pray then the children should be beaten up.